Pembuatan Website Company Profile Menggunakan CMS Wordpress Sebagai Media Promosi Travel Tour.OK - Garrin Gardiano Panandio; Heru Utomo (Jurnal Ekonomi dan Bisnis Digital, 2024)
The research method used is action research with a design process using the WebQual and Epic Model methods. Website creation application using the WordPress CMS. This research involved 20 respondents consisting of 2 web design experts and 2 computer experts who would provide an assessment of the criteria for good website design, as well as 15 consumers or potential consumers and 1 staff member from Travel Tour.OK who would provide an assessment of the effectiveness of the website design. Meanwhile, the data collection methods used were observation, interviews, questionnaires and documentation. The questionnaire results were analyzed using the Likert scale method. The results of this analysis indicate that the website design created is in the "Good" category as a company profile website on Travel Tour.OK. This is proven by the calculation results of the WebQual Index (WQI) score of 0.71 and the Epic Model score of 2.97 which is included in the "Effective" assessment category. This score shows that the website created as a company profile at Travel Tour.OK is suitable for use.